The Birth of Nationalism from Rural Landscape: An Analysis of News Documentary Films in Indonesia 1942-1945 - Tyas, Agnes Siwi Purwaning (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2024)
This paper aims to explore the significance of portraying space in narrating the independence war struggle of Indonesians people from the perspectives of film studies. In the absence of war documentaries, Japanese made newsreels produced by Nippon Eigasha Djawa or Japan Motion Picture Indonesian branch can present alternative images to discuss the war struggle. When filming the people, attention was also given to the portrayals of the space, which tend to receives less sufficient attention from the public. Nonetheless, it plays a vital role in offering a fresh viewpoint on how rural areas transform into battlefields. The study employs analysis of both visual and textual texts inside the news-documentary films to discuss three points pertaining to rural landscapes: (1) the representations of space in the films (2) the forms of interaction between space and society, and (3) the forms of activities taking place in the space in regards to independent struggle and nation founding.